The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1093/nar/gkx582
|View full text |Cite
|
Sign up to set email alerts
|

ATP hydrolysis provides functions that promote rejection of pairings between different copies of long repeated sequences

Abstract: During DNA recombination and repair, RecA family proteins must promote rapid joining of homologous DNA. Repeated sequences with >100 base pair lengths occupy more than 1% of bacterial genomes; however, commitment to strand exchange was believed to occur after testing ∼20–30 bp. If that were true, pairings between different copies of long repeated sequences would usually become irreversible. Our experiments reveal that in the presence of ATP hydrolysis even 75 bp sequence-matched strand exchange products remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 47 publications
1
39
1
Order By: Relevance
“…RecA is able to form filaments on DNA in the presence of nonhydrolysable ATP analogues; however, ATP hydrolysis is critical throughout the processes of homology search, strand exchange and RecA dissociation from DNA [35–37]. Hydrolysis of ATP provokes large‐scale conformational changes resulting in compression of the stretched active RecA filament into a state, generally referred as inactive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RecA is able to form filaments on DNA in the presence of nonhydrolysable ATP analogues; however, ATP hydrolysis is critical throughout the processes of homology search, strand exchange and RecA dissociation from DNA [35–37]. Hydrolysis of ATP provokes large‐scale conformational changes resulting in compression of the stretched active RecA filament into a state, generally referred as inactive.…”
Section: Discussionmentioning
confidence: 99%
“…RecA monomers within the whole RecA‐ssDNA filament hydrolyse ATP with k cat of 30 min ‐1 [33,34]. ATP hydrolysis by RecA was attributed to a number of processes occurring in the course of homologous recombination, including a turnover of captured duplex DNA intermediates [35], reverse exchange reaction in case of partial homology [36,37], maintaining structural integrity within the nucleoprotein filaments [38] and filament disassembly [34,39,40]. RecA is capable of promoting homologous pairing and limited strand exchange in the presence of ATPgS (nonhydrolysable ATP analogue) instead of ATP [41,42]; however, ATP hydrolysis is required for bypassing heterologous inserts [43]; in the presence of ATP hydrolysis, strand exchange is slow and unidirectional [44].…”
mentioning
confidence: 99%
“…The presence of repeated sequences in the genome can confound the homology search process. This may happen at the level of homology sampling with microhomologies or at short (< 100 bp) repeats (Danilowicz et al 2015(Danilowicz et al , 2017Lee et al 2016;Qi et al 2015) as well as at the D-loop level as many repeated DNA elements, even in the yeast genome, are larger than the minimal sequence required for efficient HR (Jinks-Robertson et al 1993;Richard et al 2008). We suggest that D-loop reversal plays a role in the donor selection process and is thus an integral component of homology search.…”
Section: Role Of Nascent D-loop Reversal In Homology Searchmentioning
confidence: 94%
“…Single-molecule observations of the E. coli RecA and human Rad51 nucleoprotein filaments dynamics revealed that filaments formed on ssDNA may reversibly interconvert between active and inactive states in response to ATP-binding and hydrolysis [ 34 , 35 , 36 , 37 ]. ATP hydrolysis is essential for the processes of homology search and strand exchange, which suggests the importance of dynamic conformational switching between the two states [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%